MATHCAD APPLICATION FOR THE MULTIDIMENSIONAL ANALYSIS OF THE INTERDEPENDENCES ON WORLD STOCK MARKETS - Marina A. Skorik (Statistika i Èkonomika, 2016)
Computer programs for analytical studies and forecasting of economic phenomena and processes are the everyday operating tool of a modern expert associated with the processing of statistical information. The program "SEMESTR" created on the base of Mathcad provides the wide range of possibilities for the comprehension of these algorithms due to automation of the multivariate data processing. Its usage in the educational process allows to develop stable skills in applying of mathematical and statistical methods of data analysis.